In-situ infrared spectroscopy as a non-invasive technique to study carbon sequestration at high pressure and high temperature. (August 2016) - Mutch, Greg A.; Anderson, James A.; Walker, Rebecca; Cerrato, Giuseppina; Morandi, Sara; Operti, Lorenza; Vega-Maza, David
Graphical abstract: Highlights: High pressure and high temperature in-situ FTIR apparatus for geological carbon sequestration. Detailed measurements of surface carbonate formation in supercritical CO2 . Surface carbonation occurs in silicate mineral analogues. Carbonate coordination to surface can be obtained. Wettability changes evidenced on exposure to CO2 . Abstract: Storage of carbon dioxide in geological formations involves changes in wettability to the host formation during injection and ultimately the formation of inorganic carbonates through mineral trapping. Sequestration locations will be at high pressure and high temperature, thus providing a challenging environment for in-situ study. However, infrared spectroscopy (FTIR) with the use of photons is not limited in temperature or pressure and therefore is applicable to study chemical changes to minerals occurring during carbon sequestration. Through the commission of a high pressure/high temperature in-situ FTIR cell and the subsequent spectroscopic following of carbonation reactions in synthesised silicate mineral analogues, we document fundamental chemical changes occurring at the nanoscale during carbon storage. Speciation, coordination of carbonate ions to the surface of silicate mineral analogues and changes in surface hydroxyl coverage are observed and discussed, in the context of CO2 injection and dissolution/mineralisation reactions of reservoir silicate minerals.